IMPLEMENTASI BIG BOOK DALAM PENINGKATAN KEMAMPUAN MEMBACA PADA KEGIATAN PLP 1 SEKOLAH DASAR - Yusraningsih Pongoliu; Siti Fadlia Imran (Program Studi Pendidikan Guru Sekolah Dasar Universitas Muhammdiyah Gorontalo, 2025)
This study describes the implementation of Big Book media in improving reading skills among second-grade students within the context of the School Field Introduction Program (PLP 1) at SDN 72 Kota Tengah. The study was motivated by the low reading fluency, limited vocabulary mastery, and weak reading comprehension observed among lower-grade students when learning was conducted through monotonous and text-only approaches. This research employed a qualitative descriptive approach using non-participant observation, field notes, informal interviews, and documentation. The data were analyzed using thematic analysis through data condensation, coding, categorization, interpretation, and conclusion drawing. The findings indicate that Big Book media strengthened students’ engagement, reading fluency, vocabulary recognition, confidence, and comprehension. The large visual display, readable text, repetitive sentence patterns, and shared-reading interaction enabled students to connect images, words, and meaning more easily. The study also introduces the concept of visual-mediated literacy engagement to explain how visual-text integration and social interaction support early reading development. Therefore, Big Book can be considered an effective and contextually relevant learning medium for improving early reading skills and creating participatory literacy experiences in elementary school PLP 1 contexts.